Discovery of novel thienoquinoline-2-carboxamide chalcone derivatives as antiproliferative EGFR tyrosine kinase inhibitors. Issue 6 (15th March 2019) - Abdelbaset, Mahmoud S.; Abdel-Aziz, Mohamed; Ramadan, Mohamed; Abdelrahman, Mostafa H.; Abbas Bukhari, Syed Nasir; Ali, Taha F.S.; Abuo-Rahma, Gamal El-Din A.
Graphical abstract: Highlights: Novel thienoquinoline-2-carboxamide-chalcone derivatives. Structural elucidation. Good Antiproliferaive Activity. EGFR-kinase inhibition. Molecular docking to ATP-binding and allosteric binding site. Abstract: Novel thienoquinoline carboxamide-chalcone derivatives were prepared via the cyclization of acylated chalcones and 2-mercaptoquinoline-3-carbaldehyde in DMF with K2 CO3 . Thienoquinolines9a–f, h exhibited promising antiproliferative effect against all the tested cell lines and gave a significant activity as EGFR inhibitors, with IC50 values ranging from 0.5 and 3.2 µM, and compounds9e and9f being the most active of the series. They also showed better activity than Erlotinib against melanoma cancer cell line A375. Moreover, compound9f influenced pre G1 apoptosis and cell cycle arrest at G2/M phase. The binding mode of the best EGFR inhibitor9e in the EGFR active site revealed that the thienoquinoline ring occupied the ATP-binding site while the chalcone moiety is located in the allosteric site and is responsible for the enhanced activity of these compounds.